Teaching of Mathematics - NCERT, (JOURNAL OF INDIAN EDUCATION, 2012)
As a part of the development of the National Curriculum Framework–2005, twenty one National Focus Groups (NFGs) were constituted to reflect upon diverse themes drawn from the area of school education. Each NFG brought out a research-based position paper. For our readers, we present here the text of the position paper on “Teaching of Mathematics”. While enlisting the main goal of mathematics education in schools on the mathematisation of the child’s thinking, the paper proposes a shift from mathematics content to mathematics learning environment offering a multiplicity of approaches, procedures and solutions. Such learning environment helps in removing fear of mathematics from children’s minds and is crucial for liberating school mathematics from the tyranny of the one right answer. The vision of excellent mathematical education, as recommended by the position paper, is based on the twin premises that all students can learn mathematics and that students need to learn mathematics.